High Frequency (10 kHz) or Burst Spinal Cord Stimulation in Failed Back Surgery Syndrome Patients With Predominant Back Pain: Preliminary Data From a Prospective Observational Study. Issue 3 (13th January 2016) - Kinfe, Thomas M.; Pintea, Bogdan; Link, Carolina; Roeske, Sandra; Güresir, Erdem; Güresir, Ági; Vatter, Hartmut
Abstract : Background: Conventional spinal cord stimulation (SCS) exhibits pain relief and improved quality of life in refractory failed back surgery syndrome. However, patients suffering from predominant back pain failed to achieve a favorable neuromodulation outcome. Currently, two new stimulation concepts, the burst and the HF10 stimulation paradigms successfully suppress intractable back pain levels in this difficult‐to‐treat subgroup. To date, literature data comparing both stimulation patterns is lacking. Methods: A prospective, observational study was conducted including 16 refractory Failed‐back surgery syndrome (FBSS) patients with previous spine surgery and predominant back pain (70% of overall pain) with or without leg pain eligible for burst or high‐frequency SCS. At baseline and at a three‐month follow‐up the pain intensity (back pain (VASB )/leg pain (VASL ), sleep quality (Pittsburgh Sleep Quality Index [PSQI]), changes in severity of depressive symptoms (Beck Depression Inventory [BDI]) and any adverse event related to the implantation and the stimulation were recorded. Results: Overall baseline VASB was significantly suppressed in 14 FBSS patients (eight burst/six patients with 10 HF10) from baseline 7.9 ± 0.7 to 2.3 ± 1 ( p < 0.001), while the overall VASL declined significantly from 3.1 ± 1.5 to 1.9 ± 0.83 ( p < 0.01). The burst patients experienced significant VASL reduction (burst 1.8 ± 0.7 ( p < 0.009) compared to HF10 patients 2.2 ± 1). Two patients failed 10 HF10‐trial. The BDI [23.3 ± 2.1 to 13.5 ± 4.5 ( p < 0.001)] and the PSQI [7.6 ± 3.7 to 4.2 ± 1.4 ( p < 0.003)] dropped down significantly for both modalities. No implantation/stimulation‐related complications were observed. Conclusions: Burst and HF10 SCS performed efficiently and safely in intractable FBSS patients with predominant back pain and deserve more refined, specific investigations to determine their efficacy.